2023
DOI: 10.1371/journal.pgen.1010798
|View full text |Cite|
|
Sign up to set email alerts
|

A novel nematode species from the Siberian permafrost shares adaptive mechanisms for cryptobiotic survival with C. elegans dauer larva

Abstract: Some organisms in nature have developed the ability to enter a state of suspended metabolism called cryptobiosis when environmental conditions are unfavorable. This state-transition requires execution of a combination of genetic and biochemical pathways that enable the organism to survive for prolonged periods. Recently, nematode individuals have been reanimated from Siberian permafrost after remaining in cryptobiosis. Preliminary analysis indicates that these nematodes belong to the genera Panagrolaimus and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Parthenogenetic Panagrolaimus nematodes analyzed in this study have been found to be triploid by Schiffer et al (2019) and other asexual representatives of the genus are also triploid (Shatilovich et al, 2023). The lower rate of differentiation among sexual lines from the MAL experiment in comparison to asexual lines could be explained by (i) lower standing genetic variation in the hermaphroditic parent at the beginning of the experiment and (ii) increased heterozygosity for asexuals arising from the third genome copy.…”
Section: Different Population Genetic Patterns Between Asexual and Se...mentioning
confidence: 63%
“…Parthenogenetic Panagrolaimus nematodes analyzed in this study have been found to be triploid by Schiffer et al (2019) and other asexual representatives of the genus are also triploid (Shatilovich et al, 2023). The lower rate of differentiation among sexual lines from the MAL experiment in comparison to asexual lines could be explained by (i) lower standing genetic variation in the hermaphroditic parent at the beginning of the experiment and (ii) increased heterozygosity for asexuals arising from the third genome copy.…”
Section: Different Population Genetic Patterns Between Asexual and Se...mentioning
confidence: 63%
“…This is a fascinating area for future research in C. elegans, as it is likely that many host-microbiome co-evolutionary processes have occurred with the dauer state. Given that the dauer stage probably acts as a transport mechanism for some bacteria, dauers could possibly help in the survival of resident microbes between discontinuous food sources [51] and across geological time scales through suspended metabolism (cryptobiosis) [52]. The microbiome is known to play a major role in the development and maintenance of host immunity.…”
Section: Understanding Factors Regulating Hostmicrobiome Interactionsmentioning
confidence: 99%
“…This strain has been isolated in North Carolina, USA by Paul Sterneberg, and is thought to be a triploid allopolyploid (3n=12) [19]. Previous studies have found it shares a common origin of parthenogenesis with most Panagrolaimus asexual strains, from a hybridization event estimated to have occurred 1.3-8.5 Million years ago [19,20]. To date, over 140 strains of the genus have been documented (NCBI Taxonomy Browser), however only nine, largely fragmented, draft genome assemblies are available on GenBank (accessed on 06.10.2023).…”
Section: Introductionmentioning
confidence: 99%
“…This widely distributed group includes strains isolated from extreme environments such as Antarctica, the volcanic island of Surtsey and the Russian permafrost. Representatives of the genus from these locations have been found to be freezing-tolerant undergoing cryptobiosis [20,21], and P. sp. PS1159 has also shown anhydrobiotic potential as a fast desiccation strategist [22].…”
Section: Introductionmentioning
confidence: 99%